TANGGUNG JAWAB ATAS WANPRESTASI PADA JASA KONSTRUKSI AKIBAT PANDEMI COVID-19 - Cok Istri Dian Laksmi Dewi (Fakultas Hukum Universitas Ngurah Rai, 2020)
COVID-19 is a global pandemic that has implications for the sustainability of the construction business. The construction service provider cannot complete the construction project due to a policy of limiting community activities. This condition causes delays in the distribution of building materials. As a result, the period of completion of development projects has been delayed. The decision to determine COVID-19 as a force majeure or not is still a legal debate. Based on the force majeure theory, the delay in project completion due to the COVID-19 pandemic is a relative force majeure ie the project completion obligation is still possible, but it is too late. This condition can be a reason for construction service providers not to pay fines for the delay.